INOVASI MEDIA DIGITAL STORY BOOK UNTUK MENINGKATKAN MAHARAH QIRA’AH BAHASA ARAB KELAS VII MTSN 3 JOMBANG - Mamluk Ahtul Hidayah; Amrini Shofiyani; Rina Dian Rahmawati; Zaki Ahmad Fauzan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to develop an interactive Digital Story Book learning media to significantly enhance Arabic reading skills (maharah qirā’ah) among seventh-grade students at MTsN 3 Jombang. Reading skills play a crucial role but are often hindered by low interest and monotonous media. The research employed a Research and Development (R&D) method utilizing the comprehensive 4D model (Define, Design, Develop, and Disseminate). Data were systematically collected through initial observations, in-depth interviews, questionnaires, pre-tests, and post-tests to measure skill improvements. The results of the material expert validation obtained an outstanding feasibility score of 90.59%, while the media expert validation reached 96.00%, both categorized as highly feasible for implementation. Field trials indicated an overwhelmingly positive student response with a score of 97.53%, proving that the media is highly engaging, user-friendly, and effective. The paired sample t-test revealed a significant difference between pre-test (average 37.23) and post-test (average 89.97) results with a p-value < 0.05, confirming that the interactive Digital Story Book effectively improves Arabic reading skills.